2018
DOI: 10.1186/s13054-018-1965-5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to prevent hemodynamic instability during renal replacement therapy in critically ill patients: a systematic review

Abstract: BackgroundHemodynamic instability related to renal replacement therapy (HIRRT) may increase the risk of death and limit renal recovery. Studies in end-stage renal disease populations on maintenance hemodialysis suggest that some renal replacement therapy (RRT)-related interventions (e.g., cool dialysate) may reduce the occurrence of HIRRT, but less is known about interventions to prevent HIRRT in critically ill patients receiving RRT for acute kidney injury (AKI). We sought to evaluate the effectiveness of RRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 62 publications
1
74
0
3
Order By: Relevance
“…In mehreren der oben bereits dargestellten Studien führte die Fiebersenkung zu einer Verbesserung der hämodynamischen Instabilität. Gerade bei Nierenersatzverfahren auf der Intensivstation scheint ein aktives Temperaturmanagement des Dialysats und des perfundierten Blutes zu einer verminderten Häufigkeit der verfahrensassoziierten hämodynamischen Instabilität beizutragen [15].…”
Section: Temperaturmanagement Bei Schwerer Kardiopulmonaler Instabilitätunclassified
“…In mehreren der oben bereits dargestellten Studien führte die Fiebersenkung zu einer Verbesserung der hämodynamischen Instabilität. Gerade bei Nierenersatzverfahren auf der Intensivstation scheint ein aktives Temperaturmanagement des Dialysats und des perfundierten Blutes zu einer verminderten Häufigkeit der verfahrensassoziierten hämodynamischen Instabilität beizutragen [15].…”
Section: Temperaturmanagement Bei Schwerer Kardiopulmonaler Instabilitätunclassified
“…International registries show that about 13% of ICU patients with AKI may require renal replacement therapies, and the mortality rate in this group could be up to 50% [8,9]. The high mortality rate in this population reflects the critical state and the development of multiorgan failure.…”
Section: Introductionmentioning
confidence: 99%
“…Using CRRT as a viable RRT has increased over the past two decades (19)(20)(21). A recent study has suggested the CRRT as the preferred RRT in AKI patients (24)(25)(26)(27)(28)(29). In patients with liver disease and intracranial hypertension, CRRT has provided better control on the fluid balance than IHD (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients need to remain immobilized during the procedure which is a disadvantage (22,23). Hemodynamic instability is a major complication that may lead to early termination of IHD and increased likelihood of morbidity and mortality in patients undergoing dialysis (2,25,26). Different dialysis methods represent variable therapeutic costs, complications, and limitations.…”
Section: Introductionmentioning
confidence: 99%